In-situ atomic layer deposition of tri-methylaluminum and water on pristine single-crystal (In)GaAs surfaces: electronic and electric structures. (31st March 2015) - Pi, T W; Lin, Y H; Fanchiang, Y T; Chiang, T H; Wei, C H; Lin, Y C; Wertheim, G K; Kwo, J; Hong, M
Abstract: The electronic structure of single-crystal (In)GaAs deposited with tri -methylaluminum (TMA) and water via atomic layer deposition (ALD) is presented with high-resolution synchrotron radiation core-level photoemission and capacitance-voltage (CV) characteristics. The interaction of the precursor atoms with (In)GaAs is confined at the topmost surface layer. The Ga-vacant site on the GaAs(111)A-2 × 2 surface is filled with Al, thereby effectively passivating the As dangling bonds. The As-As dimers on the GaAs(001)-2 × 4 surface are entirely passivated by one cycle of TMA and water. The presumed layerwise deposition fails to happen in GaAs(001)-4 × 6. In In0.20 Ga0.80 As(001)-2 × 4, the edge row As atoms are partially bonded with the Al, and one released methyl then bonds with the In. It is suggested that the unpassivated surface and subsurface atoms cause large frequency dispersions in CV characteristics under the gate bias. We also found that the (In)GaAs surface is immune to water in ALD. However, the momentary exposure of it to air (less than one minute) introduces significant signals of native oxides. This indicates the necessity of in situ works of high κ /(In)GaAs-related experiments in order to know the precise interfacial atomic bonding and thus know the electronic characteristics. The electric CV measurements of the ALD-Al2 O3 on these (In)GaAs surfaces are correlated with their electronic properties.